PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN UNIT USAHA PONDOK PESANTREN DI KOTA MATARAM - Susi Retna Cahyaningtyas; Saipul A. Muhsyaf; Rahmi Sri Ramadhani; Siti Atikah (Universitas Mataram, 2023)
Our community service provides assistance in preparing financial statements for Islamic boarding schools business units. There are many Islamic boarding schools in Indonesia. Some of them have been able to develop their internal funding sources through their economic business units. They maintain their own funding resources to generate their income. Darul XXY Islamic Boarding School built a grocery store and a mineral water shop. Why a business unit? Because these business units have the characteristics of promoting independence, making profits, creating new entrepreneurs, as well as media for developing social and community sides. This activity seeks to support Islamic boarding schools to increase the accountability of business units. Through assistance to employees and teachers in preparing financial statements, it is hoped that this activity will be able to increase the accountability and independence of business units within the Islamic boarding school environment. Indirectly, this activity is expected to encourage the creation of â€œsantripreneurâ€ in this Islamic boarding school, as well as students around Mataram City.